Low voltage CMOS power amplifier with integrated analog pre-distorter for BLE 4.0 application - Selvakumar Mariappan; Jagadheswaran Rajendran; Norlaili Mohd Noh; Harikrishnan Ramiah; Asrulnizam Abd Manaf; Shukri Korakkottil Kunhi Mohd; Yusman Mohd. Yusof (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, a low power consumption linear power amplifier (PA) for Bluetooth Low Energy (BLE) application is presented. An analogue pre-distorter (APD) is integrated to the PA. The APD consist of an active inductor, driver amplifier, and a RC phase linearizer. The PA delivers more than 12dB power gain from 2.4GHz to 2.5GHz. At the center frequency of 2.45GHz, the gain of the PA is 13dB with PAE of 26.7% and maximum output power of 14dBm. The corresponding OIP3 is 27.6dBm. The supply voltage headroom of this PA is 1.8V. The propose APD serves to be a solution to improve the linearity of the PA with minimum trade-off to the power consumption.